2020
DOI: 10.1101/2020.05.08.085027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using EEG Microstates to Examine Post-Encoding Quiet Rest and Subsequent Word-Pair Memory

Abstract: Evidence suggests that the brain preferentially consolidates memories during "offline" periods, in which an individual is not performing a task and their attention is otherwise undirected, including spans of quiet, resting wakefulness. Moreover, research has demonstrated that factors such as the initial encoding strength of information influence which memories receive the greatest benefit. Recent studies have begun to investigate these periods of post-learning quiet rest using EEG microstate analysis to observ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…In the semantic memory task, pre-stimulus EEG microstates showed correlation with known electrophysiological markers, which means they can reflect cortical activation 18 . When performing a word-pair memory task, it was observed that the network dynamics of the memory consolidation process changed EEG microstates 19 . There are also studies that have revealed the association between EEG microstates and the changes in cortical activity induced by brain stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the semantic memory task, pre-stimulus EEG microstates showed correlation with known electrophysiological markers, which means they can reflect cortical activation 18 . When performing a word-pair memory task, it was observed that the network dynamics of the memory consolidation process changed EEG microstates 19 . There are also studies that have revealed the association between EEG microstates and the changes in cortical activity induced by brain stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have supported that cognitive manipulation of EEG microstates is possible [17][18][19][20][21] . It was reported that stress response was estimated using EEG microstate sequences in psychosocial stress paradigm 17 .…”
mentioning
confidence: 99%
“…It is possible that the degree of task engagement, performance (e.g., finding two differences before the end of a trial), and other factors may have resulted in participants experiencing at least brief entry into rest-like states that were conducive to consolidation. This possibility is supported by recent neuroimaging evidence demonstrating that the brief experiencing of certain EEG microstates during post-encoding activity positively predicts subsequent memory [ 64 ]. This possibility may account for individual differences in memory performance following the filled delay though it is unlikely to account for comparable memory between our filled and unfilled delay conditions given that interference effects have been reported in related laboratory-based research [ 25 ].…”
Section: Discussionmentioning
confidence: 73%
“…Post-encoding resting state activity has been suggested to support the consolidation of memories which has, in turn, been associated with their behavioral accessibility (Tambini et al, 2010; Deuker et al, 2013; Staresina et al, 2013; Tambini & Davachi, 2013, 2019; Schlichting & Preston, 2014; Tompary et al, 2015; Gruber et al, 2016; Murty et al, 2017; Poskanzer et al, 2021). Here, we asked if post-encoding neural replay was related to memory behavior for weakly and strongly encoded memories.…”
Section: Resultsmentioning
confidence: 99%